Sound Objects - Chow, Rey; Steintrager, James A., 1965- (Book collections on Project MUSE., 2019)
Is a sound an object, an experience, an event, or a relation? What exactly does the emerging discipline of sound studies study? Sound Objects pursues these questions while exploring how history, culture, and mediation entwine with sound's elusive objectivity. Examining the genealogy and evolution of the concept of the sound object, the commodification of sound, acousmatic listening, nonhuman sounds, and sound and memory, the contributors not only probe conceptual issues that lie in the forefront of contemporary sonic discussions but also underscore auditory experience as fundamental to sound as a critical enterprise. In so doing, they offer exciting considerations of sound within and beyond its role in meaning, communication, and information and an illuminatingly original theoretical overview of the field of sound studies itself.